2019
DOI: 10.1159/000501825
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Electromyography and Digital Palpation Measurement of Pelvic Floor Muscle Strength in Postpartum Women with Stress Urinary Incontinence and Asymptomatic Parturients: A Cross-Sectional Study

Abstract: <b><i>Aims:</i></b> Early evaluation of pelvic floor muscle (PFM) in postpartum women is important for the treatment of stress urinary incontinence (SUI). Digital vaginal palpation and electromyography (EMG) evaluation based on Glazer protocol are widely used for the assessment of PFM. However, the correlation among digital palpation, EMG, and morbidity of postpartum SUI is still unclear. This study aims to investigate the relationship between postpartum SUI and PFM examinations. <b&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…The examination includes voluntary (will-dependent) contraction, used during PFM training, and involuntary (will-independent) contraction, occurring during increased intra-abdominal pressure [ 30 , 31 ]. The physiotherapist may also use EMG, perineometer, and palpation to evaluate the PFM function [ 32 , 33 ]. The perineometer is used to assesses vaginal pressure, while the EMG records the electrical activity of muscle fibers [ 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The examination includes voluntary (will-dependent) contraction, used during PFM training, and involuntary (will-independent) contraction, occurring during increased intra-abdominal pressure [ 30 , 31 ]. The physiotherapist may also use EMG, perineometer, and palpation to evaluate the PFM function [ 32 , 33 ]. The perineometer is used to assesses vaginal pressure, while the EMG records the electrical activity of muscle fibers [ 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The physiotherapist may also use EMG, perineometer, and palpation to evaluate the PFM function [ 32 , 33 ]. The perineometer is used to assesses vaginal pressure, while the EMG records the electrical activity of muscle fibers [ 32 , 33 , 34 ]. PFM palpation is a common, fast, and inexpensive examination which should be performed by an experienced therapist.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the results in these earlier articles show higher levels of activity in the PFM than observed in the current study; however, the mean age of the participants in the earlier studies was lower than in the present study. A large number of reports emphasize the fact that PFM activity decreases with age [ 8 , 9 , 15 , 16 ]. Only one paper describes the PFM activity of women with SUI at a similar age (mean 66.1 ± 8.7 years) to those described in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Digital vaginal palpation and sEMG evaluation are two common methods to evaluate the strength of PFM. Yang X et al [8] assessed 1,380 parturients at 6-8 postpartum weeks by using both vaginal palpation and sEMG. Results showed that the contraction variables of EMG had a significant correlation between them and sEMG was also correlated with SUI.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proved that supervised training protocol is more effective than oral instruction alone. Digital palpation and surface Electromyography (sEMG) recordings are often applied to teach PFM contraction and evaluate the effect of PFMT [8][9] . This study investigates the therapeutic effect of at-home PFM training combined with in-hospital electrical stimulation plus biofeedback therapy on Chinese primipara with SUI in the short-term postpartum period.…”
Section: Introductionmentioning
confidence: 99%